208k views
1 vote
Simplify the expression.
4(20 + 12 ) divide by (4 - 3)

User Hjchin
by
5.1k points

2 Answers

1 vote

Now, taking this into account, we can begin to solve the problem, starting with the equations in the parenthesis. By doing this, we get the following: 4(32)/(1).

Next, we check to see if there are any exponents involved in the equation, which there aren't, so we can move on the multiplication and division. In this case there are multiplication and division in the problem, so we go from left to right. The equation then becomes 128/1, which is 128.

So the answer to the equation is 128.

User Manzana
by
5.7k points
7 votes

4(20 + 12 ) ÷ (4 - 3)

= 4( 32) ÷ (1)

= 4( 32)

= 128 <============== answer

User NinMonkey
by
5.3k points